DEMOGRAPHIC TECHNIQUES FOR EDUCATIONAL RESEARCH - BILLS, David (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
We will spend a lot of time reading and discussing demographic research, with the goals of understanding why the researchers chose the methods and data that they did, how these methods work, and how we can replicate them. We will read several expository articles on how to "do" demographic research, and will get our hands dirty as much and as often as we can. By the end of the semester, you should be able to read at a reasonable level of comprehension research that uses demographic techniques and have begun to develop the ability to design and conduct your own demographic analyses.